Biogeographic variation in the impact of predation and secondary foundation species on the recruitment and growth of sessile mangrove prop root communities - Aquino-Thomas, Jessene; Sears, Shalondria J.; Proffitt, C. Edward (Frontiers in Marine Science, 2025)
Predation and secondary foundation species play crucial roles in structuring sessile mangrove prop root communities. However, their relative importance and their interactions across biogeographic gradients remain poorly understood. This study investigated the impact of predation and secondary foundation species on mangrove prop root epibiont assemblages along a latitudinal gradient in Florida. Predator exclusion treatments were deployed at four sites spanning tropical to temperate zones, and community development was monitored over 6 months. The results showed that the effects of predation shifted with latitude, from increasing the species richness in the south while reducing it in the north. Secondary foundation species, such as sponges, oysters, and barnacles, generally outcompeted other species for space in the early colonization stages, but tended to increase biodiversity when space was not limiting. Secondary foundation species also exhibited context-dependent associations with species richness across the latitudinal gradient. Sponges and oysters tended to enhance the species richness under reduced predation pressure, while barnacles generally had negative effects at higher latitudes. The multivariate analyses revealed that the interaction between predation and latitude explained more variation in the community structure than predation alone, and secondary foundation species contributed significantly to these patterns. The findings support the predation hypothesis and facilitation by secondary foundation species in shaping mangrove prop root community shifts across biogeographic gradients, providing insights into the complex interactions structuring mangrove epibiont communities.